Adsorption of Pb(II) from Aqueous Solutions onto Humic Acid Modified by Urea-Formaldehyde: Effect of pH, Ionic Strength, Contact Time, and Initial Concentration - Meidita Kemala Sari; Rahmat Basuki; Bambang Rusdiarso (Universitas Gadjah Mada, 2021)
Humic acid (HA) and urea-formaldehyde (UF) have been frequently reported as heavy metal adsorbents. However, the literature has never written HA modification by UF to improve the adsorbent’s performance. In this study, a new adsorbent of humic acid-urea formaldehyde (HA-UF) was synthesized. The reaction of the conducted the formation of HA-UF –COOH group of HA with the –NH2 group of UF was evidenced by decreasing total acidity from 549.26 cmol/kg (in HA) to 349.30 cmol/kg (in HA-UF). The success of HA-UF formation was characterized by attenuated total reflection-infrared (ATR-IR), energy dispersive X-Ray (EDX), and X-ray diffraction (XRD). The high stability of HA-UF was shown by 96.8% remaining in solid form at pH 12.4. Adsorption behavior of Pb(II) onto HA-UF was influenced by the ionic strength and pH, which were mainly driven by the ion exchange mechanism (EDR = 9.75 kJ/mol). The higher ionic strength will affect decreasing adsorbed Pb(II) at the optimum pH of 5.5. The effect of initial Pb(II) concentration (isotherm) shows that the data fitted well with the Langmuir-b isotherm model indicated the monolayer adsorption of Pb(II) onto homogenous surfaces of the HA-UF with the adsorption capacity of 2.26 × 10–4 mol/g (which is higher than its original HA of 1.12 × 10–4 mol/g). The Ho (pseudo-second-order) kinetics model represented the effect of contact time (kinetics) was represented by the Ho kinetics model. The synthesized adsorbent is also reusable, with 88.59% of adsorption capacity remaining in the fifth recycle run. Therefore, the adsorbent of HA-UF is suggested to be a promising candidate for adsorption applications.